Choroidal neovascular membrane inhibition in a laser treated rat model with intraocular sustained release triamcinolone acetonide microimplants. Issue 8 (24th July 2003) - Ciulla, T A; Criswell, M H; Danis, R P; Fronheiser, M; Yuan, P; Cox, T A; Csaky, K G; Robinson, M R
Abstract : Aim: To determine if intravitreal microimplants containing triamcinolone acetonide (TAAC) inhibit experimental fibrovascular proliferation (FVP) induced by laser trauma in a rat as a model of choroidal neovascular membranes (CNVMs). Methods: 20 anaesthetised male Brown Norway rats received a series of eight krypton red laser lesions per eye (647 nm, 0.05 s, 50 μm, 150 mW). Three types of sterilised TAAC microimplant designs were evaluated: implant A consisting of 8.62% TAAC/20% polyvinyl alcohol (PVA) matrix (by dry weight); implant B consisting of 3.62% TAAC/20% PVA matrix; and implant C consisting of a dual 8.62% TAAC/20% PVA matrix design combined with a central core (0.5 mm) of compressed TAAC to extend the implant release time. For each animal studied, one eye received one of the three aforementioned TAAC implant designs, while the fellow eye received a control implant consisting of PVA but without TAAC. The animals were sacrificed at day 35 and ocular tissues were processed for histological analysis. Serial histological specimens were methodically assessed in a masked fashion to analyse each laser lesion for the presence or absence of FVP; maximum FVP thickness for each lesion was measured from the choriocapillaris. Results: All three types of TAAC implants inhibited FVP relative to controls in a statistically significant fashion. In the eyes that received implant A (n = 8), the mean thickness of the recovered lesions (n = 36) measured 32 (SD 22) μm, compared to 52 (30) μm (p <0.005) for the recovered lesions (n = 40) from the fellow control eyes. In the eyes that received implant B (n = 6), the mean thickness of the recovered lesions (n = 31) measured 28 (15) μm, compared to 50 (29) μm (p <0.001) for the lesions (n = 19) recovered from the fellow control eyes. In the eyes that received implant C (n = 6), the mean thickness of the recovered lesions (n = 21) measured 39 (24) μm, compared to 65 (30) μm (p <0.001) for the lesions (n = 39) recovered from the fellow control eyes. Conclusions: All three of the tested TAAC microimplant designs produced potent inhibition of FVP in a rat model of CNVMs. There were no differences in inhibition of FVP between the three different types of implants evaluated. This study provides evidence that: (1) corroborates previous investigations that propose TAAC as a potential treatment for CNVMs in humans, and (2) demonstrates TAAC can be effectively delivered via long acting sustained release intraocular microimplants. It should be noted, however, that the FVP observed in this rat laser trauma may not reflect the CNVM observed in human with exudative age related macular degeneration (AMD).